Strategi Pemasaran dalam Peningkatan Penjualan Boneka pada Pengusaha Toko Boneka di Kecamatan Sukajadi Kota Bandung - Pratidhina, Puti Harissa; Bramasto, Ari; Suhayati, Ely (Jurnal Pengabdian Tri Bhakti, 2022)
Bonsuka is a doll business brand located in the Sukamulya area, Sukagalih Village, Sukajadi District, Bandung. The preliminary survey conducted identified problems at the Doll Shop, including that so far Bonsuka did not have a marketing strategy that was recorded according to external and internal conditions at the company to prevent changes in the business environment, sales volume has not been maximized due to the Covid-19 pandemic which has been going on for 2 years more.. Hope The community service program that we hope will be able to socialize marketing strategies in increasing sales and provide assistance to partners introducing their products through social media